Study on the Satisfaction Level of Heritage and Cultural Tourism Information Available in Media - Obaid Rashid Aldhanhani, Howaidah Mohamed; Zahir Zainudin, Mohamad (International Journal of Sustainable Construction Engineering and Technology, 2022)
Sharing information and provide access to all societies can promote heritage and cultural tourism. Especially, using media and social networks, and the proliferation of smart devices. Through new media such as online sites and publications, visitors and tourists to heritage promotions are better able to obtain adequate information about the heritage sites. Furthermore, marketers can better collect critical information from customers online and solicit feedback on cultural experiences. Hence, this paper presents a study on determine the level of satisfaction amongst residents of UAE on the heritage and cultural tourism information that had made available through various media. The study was conducted quantitatively, with data collected via questionnaire surveys. A total of 501 completed questionnaires were obtained and analysed statistically. It was found that five most influential questions on the satisfaction level of respondents on the heritage and cultural tourism information available in media are as followed. The top rank is for question 11 which is I would recommend to attend culture events in UAE for all people I know on my social media accounts. Then follows second rank that is question 7 which is Young Emirati people always share in culture events and share on thier social media accounts. The third rank is for question 8 wich is We are always satisfied with information about events in UAE related to heritage and culture events. The fouth rank is question 9 which is Heritage and culture events have the top priority in society and attract all Emirati people. And the fifth rank is question 6 wich is Government authorities plan for effective events that promote culture and heritage tourism. It can be concluded that majority of respondents were pleased with the information provided and expressed a willingness to recommend online sources to their friends. A sizable proportion of those polled emphasised the importance of better information in promoting heritage and cultural tourism in the UAE.